Browning's "A Forgiveness": A Grammatical Reading. Issue 2 (February 2014) - Gibson, Richard
Abstract This reading situates Robert Browning's "A Forgiveness" in the context of popular Victorian lyrics in order to draw attention to features of the popular texts that are tellingly absent from or ironized within Browning's poem. I trace the "grammar of forgiveness" in the popular texts, outlining the often explicitly theological framework that guides how the language of forgiveness is used and to what intended effect. This linguistic exploration also demonstrates that Browning's title – now a curious phrase – was not unusual at the time; it was often employed in the period to make distinctions between human and divine forgiveness. The study juxtaposes the "grammar of forgiveness" found in the popular texts with that of Browning's poem, revealing that the speaker is, in his own macabre fashion, grammatically inventive, fusing forgiveness and retribution in his deadly response to his wife's feigned infidelity and the murderous visit to confession in which he reports how his wife died. Yet the speaker's bleak presentation of forgiveness, I argue, should not be read uncritically as expressing Browning's ethical perspective. Instead, I observe that the poem's form – the dramatic monologue – presents the reader with the opportunity for critique of the speaker's project, inviting reflection on the speaker's form of forgiveness rather than demanding its practice in the manner characteristic of the popular lyrics.